(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Sviluppo tecnologico, internet e dinamiche interculturali - 2. I nuovi mezzi di comunicazione sociale nel magistero della Chiesa cattolica - 3. Strategie confessionali e prospettive interculturali: il caso delle app religiose - 4. Il download di una app tra tutela della privacy e sicurezza sociale. Internet, Cultures, Religions. Some insights for an intercultural web. ABSTRACT: The article aims to investigate the relationship between the Internet and religions. Technological evolution has produced important consequences on society and relationships between people, also involving religious denominations. The latter have defined new ways of professing and excercizing their belief: creation of Christian communities on line, Internet as window of knowledge of monastic life or proselytizing tools, propaganda through religious videogames, app for smartphones and tablets. Such tools can contribute to the formation of an intercultural web. The use of the Internet and of modern technologies questions jurists about the protection of sensitive data of religious interest and of social security. Downloading an app on smatphones and tablets allows the provider to access even the user’s sensitive data, including their religious affiliation. This requires the intervention of Italian Data Protection Authority, whose task is to check whether the processing of sensitive data is carried out in compliance with the applicable regulations. The improper use of the Internet can also involve the protection of social security, through the denigration of a particularly weak social group and as a tool of spreading and inciting hatred (hate speech). The legislator is therefore called upon to define the sanctioning capacity of the existing legal systems.